2023
DOI: 10.3390/gels9090742
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin/Hyaluronic Acid Photocrosslinked Double Network Hydrogel with Nano-Hydroxyapatite Composite for Potential Application in Bone Repair

Jianuo Zheng,
Yunping Wang,
Yuwen Wang
et al.

Abstract: The application of hydrogels in bone repair is limited due to their low mechanical strength. Simulating bone extracellular matrix, methylacrylylated gelatin (GelMA)/methylacrylylated hyaluronic acid (HAMA)/nano-hydroxyapatite(nHap) composite hydrogels were prepared by combining the double network strategy and composite of nHap in this study. The precursor solutions of the composite hydrogels were injectable due to their shear thinning property. The compressive elastic modulus of the composite hydrogel was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…As the main component of ECM, it exists in skin, cartilage, vitreous and other tissues and participates in inflammation and angiogenesis [ 48 , 49 ]. Due to its unique viscoelasticity, good biocompatibility, biodegradability and hydrophilicity, hyaluronic acid also displays great potential in regenerative medicine [ 50 , 51 ]. Typically, hydrogels composed of hyaluronic acid exhibit loose binding between side chains, leading to a soft structure and low strength, making them susceptible to hydrolysis and degradation [ 51 , 52 ].…”
Section: Types Of Photo-crosslink Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the main component of ECM, it exists in skin, cartilage, vitreous and other tissues and participates in inflammation and angiogenesis [ 48 , 49 ]. Due to its unique viscoelasticity, good biocompatibility, biodegradability and hydrophilicity, hyaluronic acid also displays great potential in regenerative medicine [ 50 , 51 ]. Typically, hydrogels composed of hyaluronic acid exhibit loose binding between side chains, leading to a soft structure and low strength, making them susceptible to hydrolysis and degradation [ 51 , 52 ].…”
Section: Types Of Photo-crosslink Hydrogelsmentioning
confidence: 99%
“…Typically, hydrogels composed of hyaluronic acid exhibit loose binding between side chains, leading to a soft structure and low strength, making them susceptible to hydrolysis and degradation [ 51 , 52 ]. However, the physical and chemical properties of hyaluronic acid changed by modifying the active groups such as hydroxyl group and carboxyl group on the molecule [ 50 ]. For example, after the methacrylate group is introduced to the hyaluronic acid chain, the hyaluronic acid chain can be photo-crosslinked under ultraviolet ( ) light irradiation, so as to form a hyaluronic acid hydrogel with higher strength that supports other bioactive factors, called HAMA hydrogel [ 53 ].…”
Section: Types Of Photo-crosslink Hydrogelsmentioning
confidence: 99%
“…Furthermore, the smaller building blocks and aggregation of nanograins in biogenic aragonite create strong boundary effects, further increasing their hardness compared to geologic aragonite. By mimicking the features of biominerals, such as the nanostructuring of minerals and mixing with organics or other minerals, researchers reinforce the structure and improve the overall mechanical properties [ 119 , 120 , 121 , 122 ]. Specifically, inspired by the stabilized ACC of crustacean cuticles, Wu et al reported the efficient ACC stabilization ability of the most abundant biopolymer cellulose nanofibers (CNFs) [ 123 ].…”
Section: Classification Of Biomaterials Used In Regenerative Medicinementioning
confidence: 99%